A Persistent Deep Anticyclonic Vortex in the Rockall Trough Sustained by Anticyclonic Vortices Shed From the Slope Current and Wintertime Convection. Issue 10 (22nd October 2020) - Smilenova, Angelina; Gula, Jonathan; Le Corre, Mathieu; Houpert, Loïc; Reecht, Yves
Abstract: The presence of a persistent surface anticyclone centered at approximately 55°N, 12°W in the Rockall Trough, northeast North Atlantic, has been previously noted in satellite altimetry data. Here, we show that this surface anticyclone is the imprint of a deep, persistent, non‐stationary anticyclonic vortex. Using wintertime 2007 and 2011 ship‐board data, we describe the anticyclone's vertical structure for the first time and find that the anticyclone core is partly made of warm and salty Mediterranean Overflow Water. The anticyclone has a radius of 40 km, it stretches down to 2, 000 m, with a velocity maximum around 500 m. To analyze the anticyclone's generating mechanism, we use a mesoscale‐resolving ( 2 km) simulation, which produces a realistic pattern of the Rockall Trough anticyclone. The simulation indicates that the anticyclone is locally formed and sustained by two types of processes: wintertime convection and merger with anticyclonic vortices shed from the slope current flowing poleward along the eastern Rockall Trough slope. Intense negative vorticity filaments are generated along the Rockall Trough south‐eastern slope, and they encapsulate Mediterranean Overflow Water as they detach and grow into anticyclonic vortices. These Mediterranean Overflow Water‐rich vortices are advected into the trough, consequently merging with the Rockall Trough anticyclone and sustaining it. We suggest that the Rockall Trough anticyclone impacts regional intermediate water masses modifications, heat and salt budgets locally, and further afield into the neighboring subpolar northeast North Atlantic. Plain Language Summary: Water masses of different origins converge in the Rockall Trough, a deep bathymetric depression in the northeast North Atlantic, and undergo transformations with direct implications for the inflow of warm water into the Nordic Seas. We use in situ observations to document, for the first time, the vertical structure of a subsurface anticyclone, which is a clockwise oceanic vortex in the trough. We show that the anticyclone has a radius of 40 km, extends down to 2, 000 m, with a velocity maximum at 500 m depth. Its core is made of warm and salty Mediterranean water. We use outputs from a high‐resolution ( 2 km) realistic simulation to study the mechanisms driving the anticyclone. We show that the anticyclone is impacted predominantly by two different processes. One is the wintertime convection, which mixes waters from the surface down to 1, 000 m inside the anticyclone. The other is the merger with smaller vortices that pinch off the slope current flowing northward along the Porcupine Bank, south of the Rockall Trough, and feed the anticyclone with water masses of Mediterranean origin. We showcase the potential impact of the anticyclone on the regional and nearby northeast North Atlantic heat and salt distributions. Key Points: A persistent, non‐stationary, deep anticyclonic vortex is identified in the central Rockall Trough using in situ, satellite and model data The anticyclone has a velocity maximum around 500 m and reaches down to 2, 000 m depth; its core is predominantly made of warm and salty MOW The anticyclone is sustained by the merging of MOW‐rich vortices shed from the slope current and wintertime convection